Detection of Coffee Bean Damage in The Roasting Process Based on Shape Features Analysis. (July 2020) - Gunadi, I G A; Artha, I P M K; Christyaditama, I G P; Wicaksana, G A S; Martina, I M
Abstract: Many studies raise the issue of analysis on the quality of coffee beans (green beans). Green beans are the term used to indicate coffee beans before roasting. The importance of analyzing the quality of coffee beans not only in coffee beans but also in rice seeds. Rice seeds are used as a mixture in the roasting process of coffee. Analysis of the quality of roasted coffee is very important. In roasted coffee beans can be damaged and changes to the coffee beans. Some types of damage to coffee beans include, blackened seeds, partially blackened seeds, browned seeds, broken seeds, perforated seeds, epidermis seeds, horned skin seeds, too young seeds, spotted seeds, and dirty seeds. This study focuses on one of the damage factors, namely broken coffee beans after broken beans. In this study, analysis of roasted coffee quality was determined by shape analysis. The shape analysis uses elongation values. there are two categories of classification, the first class of coffee is of good quality, and the second is coffee with poor grade. Classification is good if the elongation value is more than 0.85, for other conditions it is classified as bad. The results of this study have the following accuracy values, at coffee with a classification of good accuracy of 93.4%, while those at coffee with a bad classification of accuracy are 78.5%.